Global trends in the development of monitoring systems for mobile agricultural equipment - Goltyapin Vladimir; Golubev Ivan (E3S Web of Conferences, 2020)
In this paper, systems for remote monitoring of equipment from various manufacturers are analyzed. Such systems are currently offered by a number of manufacturers of tractors and other mobile agricultural equipment. They are designed to management the operation of a diesel engine; hydraulic transmission management; management of working bodies (maybe several); active security; comfort and climate control; navigation, communications and other multimedia systems. However, in the literature there is no system analysis of them. Therefore, the aim of the study is to analyze and generalize advanced solutions in the development of remote monitoring systems of the largest domestic and foreign manufacturers of agricultural machinery and equipment. The development of remote monitoring systems of domestic and foreign manufacturers, including those awarded at the International agro-industrial exhibitions, were analyzed and summarized. The authors summarized the characteristics of monitoring systems and showed their application areas. The article discusses innovative telemetry and monitoring systems for agricultural machinery, which allow optimizing the process, making adjustments to the settings, planning maintenance, saving fuel, and increasing productivity.